Racial and Ethnic Diversity in Academic Emergency Medicine: How Far Have We Come? Next Steps for the Future. (3rd December 2018) - Boatright, Dowin; Branzetti, Jeremy; Duong, David; Hicks, Marquita; Moll, Joel; Perry, Marcia; Pierce, Ava; Samuels, Elizabeth; Smith, Teresa; Angerhofer, Christy; Heron, Sheryl
Abstract: Although the U.S. population continues to become more diverse, black, Hispanic, and Native American doctors remain underrepresented in emergency medicine (EM). The benefits of a diverse medical workforce have been well described, but the percentage of EM residents from underrepresented groups is small and has not significantly increased over the past 20 years. A group of experts in the field of diversity and inclusion convened a work group during the Council of Emergency Medicine Residency Program Directors (CORD) and Society for Academic Emergency Medicine (SAEM) national meetings. The objective of the discussion was to develop strategies to help EM residency programs examine and improve racial and ethnic diversity in their institutions. Specific recommendations included strategies to recruit racially and ethnically diverse residency candidates and strategies to mentor, develop, retain, and promote minority faculty.